Psoralea bituminosa var. atropurpurea (Psoraleeae, Fabaceae) from Morocco recognised as a distinct species in Bituminaria - Bogdanović, Sandro; Brullo, Cristian; Brullo, Salvatore; Cambria, Salvatore; Giusso Del Galdo, Gianpietro (Phytotaxa, 2020)
Within taxonomic studies on the genus Bituminaria in Morocco, a population previously attributed to Psoralea bituminosa var. atropurpurea is examined. Basing on morphological investigations carried out on living and herbarium material coming from the type locality, it is treated as a distinct species and here proposed as Bituminaria atropurpurea comb. et stat. nov. This species differs from B. bituminosa s.str., as well as from other known taxa of the genus, in several features of the leaves, inflorescence, flowers and pods, as well as the micro-morphology of seeds, pods and pollen grains. Its distribution, ecology and relationships with B. antiatlantica and other allied species, such as B. basaltica and B. tunetana, are also examined. Besides, its detailed iconography and an analytical key of the species currently ascribed to this genus are provided.